Organizacja więziennictwa polskiego (1918-1939) - Chmielewski, Krzysztof; Pająk, Maciej (Czasopismo Prawno-Historyczne, 2018)
Recovering after the partition period, the Polish state faced many challenges and one of them definitely was the penitentiary policy. Among the legacies of the period of partition were three different prison systems and different regulations in the field of penitentiary law. The main task of the Polish legislator was to unify the national prison system by taking into account not only the specificity of the existing solutions but also the achievements of the contemporary penitentiary. The purpose of the paper is to present the history of the organization of the Polish prison system between 1918 and 1939 in more detail. It is necessary to describe the political situation in the Polish lands during the final years of the First World War which significantly influenced the different character of the institutions in the Polish territories. The reflections on the organization of the Polish prisons during the interwar period will be centered around the following issues: taking over prisons by the Polish authorities, systematic unification of the structure of the prison system, prison stratification, the legal status of the prison staff, the education system of prison officers as well as the system of supervision of the execution of prison sentences. The literature on the subject highlights the importance of the international penitentiary congresses for the development of the penitentiary law in the interwar period. The contribution of the Polish delegations to the works of the London, Prague and Berlin congresses was significant. Taking into account the importance of the resolutions of the congresses, the paper will present the participation of Poles in the debates. Research methodology is based on the analysis of normative acts devoted to the organization of the Polish prison system between 1918 and 1939. The following are among the analyzed elements: the decree on the provisional prison regulations of the 8th of February 1919, the regulation by the President of the Republic of Poland on the organization of the prison system of the 7th of March 1928, the regulation by the Minister of Justice on the rules and regulations of the prison system of the 20th of June 1931, the regulation by the President of the Republic of Poland on the Prison Guard of the 23rd of August 1932, and the act on the organization of the prisoner system of the 26th of July 1939. Memories of persons involved in prison activity and publications pertaining to penitentiary law issues from the interwar period were also used to prepare this article.